INTERNATIONAL LEGAL STANDARDS FOR THE PROVISION OF PUBLIC SERVICES - Korniakova, Tetiana; Berezhna, Kateryna; Kobrusieva Yevheniiа; Lakhova, Olena; Lytvyn, Olena (Gênero & Direito, 2020)
The scientific article is devoted to the coverage of international legal acts and standards in European and international practice for the provision of public services as a direction of reforming legal education in Ukraine. The directions of improving domestic legislation on the provision of public services taking into account international legal standards are proposed: the development of the theory of public services, which consists in consolidating conceptual and categorical provisions in the Concept of public services, principles of public services, quality criteria for the provision of public services, and the like; unification of the legal regulation of administrative procedures by adopting the Administrative Procedure Code of Ukraine, which would clearly disclose the issue of providing public services; fixing in the legal acts the types of legal guarantees to ensure the legality of the provision of public services: monitoring the activities of public administration entities on the provision of public services; holding public servants accountable for refusing to provide a certain type of public service; bringing into line with European experience the requirements for adoption, amendment, cancellation and the possibility of appealing individual administrative acts that are the results of the provision of public services; decentralization of power, which consists in justifying an increase in the powers of local authorities in comparison with public authorities.